MENERAPKAN PEMAHAMAN LINTAS DALAM PENDIDIKAN - Fauziah Khairani Lubis (BAHAS, 2015)
The understanding of the variety of culture that exists in the world is crucial since the meeting of people from one country to the other countries is inevitable nowadays with the improvement of knowledge and technology. Therefore since young age, a child is suggested to be given knowledge about the different culture including manners, ethics, taboos, norms that exist  in  the world. The cultural understanding promotes tolerance, ability to work with other people, good entrepreneurship skills and most of all, peace. The teaching of the values of tolerance should be started since a student is in an elementary level. The concept of ‘seni budaya’ classes should be changed into classes with more emphasis on the cross cultural understanding, rather than merely doing some art projects.   Keywords: improvement of knowledge and technology,  cultural understanding, tolerance